Similar levels of symptoms and problems were found among patients referred to specialized palliative care by general practitioners and hospital physicians: A nationwide register-based study of 31, 139 cancer patients. (September 2020) - Hansen, Maiken Bang; Ross, Lone; Petersen, Morten Aagaard; Adsersen, Mathilde; Rojas-Concha, Leslye; Groenvold, Mogens
Background: Previous studies suggest that the symptomatology threshold (i.e. the level and types of symptoms) for a referral to specialized palliative care might differ for doctors in different parts of the healthcare system; however, it has not yet been investigated. Aim: To investigate if the number and level of symptoms/problems differed for patients referred from the primary and secondary healthcare sectors (i.e. general practitioner versus hospital physician). Setting/participants: Adult cancer patients registered in the Danish Palliative Care Database who reported their symptoms/problems at admittance to specialized palliative care between 2010 and 2017 were included. Ordinal logistic regression analyses were performed with each symptom/problem as outcome to study the association between referral sector and symptoms/problems, controlled for the effect of gender, age, cancer diagnosis and the specialized palliative care service referred to. Results: The study included 31, 139 patients. The average age was 69 years and 49% were women. Clinically neglectable associations were found between referral sector and pain, appetite loss, fatigue, number of symptoms/problems, number of severe symptoms/problems (odds ratios between 1.05 and 1.20, all p  < 0.05) and physical functioning (odds ratio = 0.81 (inpatient care) and 1.32 (outpatient), both p  < 0.05). The remaining six outcomes were not significantly associated with referral sector. Conclusion: Differences across healthcare sectors in, for example, competences and patient population did not seem to result in different symptomatology thresholds for referring patients to palliative care since only small, and probably not clinically relevant, differences in symptomatology was found across referral sectors.